Performance Audit of Supplementary Nutrition Program under ICDS in Assam (2002-2007) - CAG of India (CAG of India, 2008)
The problem of malnutrition amongst children in Assam is being addressed through Supplementary Nutrition Programme (SNP), a constituent component of a package of services under ICDS. A performance review of the “Nutrition Programme under ICDS” revealed the following shortcomings: 1. The State Government did not provide funds for Supplementary Nutrition Programme from 2002-03 to 2004-05. The Additional Central Assistance of Rs. 135.86 crore for nutrition meant exclusively for children below 3 years was diverted for providing nutrition for all groups of beneficiaries. 2. Performance of the SNP in terms of nutritional supplementation vis-à-vis prescribed feeding days was grossly inadequate. Poor delivery of nutrition supplementation at only 21-29 percent (calories) and 24 to 33 percent (protein) negated the programme objectives. 3. The programme implementation remained disappointing, often being handicapped by long spells of non-feeding days, inequality in allotment of nutritious food, diversion of allotment of foodstuffs without compensatory replacement and expenditure in excess of norms. 4. RTE weighing 2,32,708 kgs valued at Rs.86.10 lakh were diverted without corresponding compensatory replacements thereby depriving 1,99,020 beneficiaries of 46 projects of supplementary nutrition indicating lack of control in programme management. 5. Despite subsidized PDS (APL) rice being abundantly available, the Department procured SNP rice at higher rates resulting in avoidable expenditure of Rs. 11.69 crore. 6. Overlooking a cheaper rate for RTE offered by a manufacturer the Department procured the item at higher rate consecutively for three years by repeated extension of time of the contact resulting in an avoidable expenditure of Rs. 2.85 crore.
For the Period 2002-03 to 2006-07